The Cost Analysis of a 7-Year Cross-Section of Patients with Epilepsy in a Single-Center Child Neurology Outpatient Clinic: A Descriptive Retrospective Analysis - Yilmaz, Arzu (Journal of Pediatric Epilepsy, 2022)
The cost analysis of the 7-year cross-section of the patients in pediatric neurology outpatient clinic including patients with foreign nationality was investigated retrospectively. Between January 10, 2013 and January 10, 2020, the total number of applicants, the nationalities of the patients, and the hospital cost were analyzed. Of 3,338 patients, aged between 0 and 20 years with mean age of 8.7 years at admission to the child neurology had received 17,476 clinical examinations. Of these, 51.6% were male and 93.5% cases were Turkish patients (n = 3,122), with 6.5% foreign nationals (n = 216). There was no difference in terms of gender between nationalities (p > 0.05). The total cost of cases with epilepsy was 1,312,427.73 Turkish Lira (TRY) and 6.2% account belonged to foreign nationals, mostly from Iraq (3.6%, n = 119) and Syria (2.4%, n = 80). The highest proportion of foreigner admissions due to epilepsy was in 2018 (11.1%). Mean average of health expenditures for foreign nationals diagnosed with epilepsy was 6.2% with the highest expenditure in 2019 (27.750,06 TRY). The proportion of admissions for epilepsy was 27.6% (17,476/63,173) among all neurological admissions. The proportion of Turkish patients was 25.6% (6,181/63,173), and 3.8% (1,295/3,398) accounted for foreigners' admissions. The proportion of total epilepsy costs compared with the total neurological admissions was 30% (1.312.427,73 TRY/4.347.592,80 TRY) and among them, the expenditure proportion for epilepsy in Turkish patients compared with that of total foreigner admissions was 3.9% (80.416,44 TRY/201.490,515 TRY). Expenditures for evaluating of epileptic children with foreign nationality cover an average of 6.5% of the entire section of the health expenditures made for patients with the diagnosis of epilepsy in the pediatric neurology outpatient clinic over the 7-year period. Epilepsy accounts for 30% admissions among all neurological admissions with 3.9% belonging to foreign national admissions.
Keywords: health services; child; adolescents; foreign nationality; refugees